The organizing learning activities using creativity as a base to promote competency to create innovation for mathayomsuksa 3 students - Soongpol, Piangjai; Phorntaweekul, Satjatham (Journal for Developing the Social and Community, 2023)
The purposes of this research were 1) to find the effectiveness of learning activities using creativity as a base for Mathayomsuksa 3 students, the efficiency according to the criteria 70/70 2) Comparison of the competency to create innovation using creativity as a base for Mathayomsuksa 3 students with 70 percent criteria 3) to study students' satisfaction with learning activities using creativity as a base to promote the competency to create innovation for Mathayomsuksa 3 students with learning activities using creativity as a base to promote innovation for students in Mathayomsuksa 3, Kukasingprachasan School 22 students studying design and technology in the second semester of the academic year 2020. The experimental period was 20 weeks. The research instruments consisted of 1) Plans for learning activities 2) Innovation Ability Assessment Form 3) Satisfaction assessment form the statistics used to analyze the data were mean, percentage, and standard deviation. The results of the research were as follows: 1) Finding the efficiency of learning activities using creativity as a base for Mathayomsuksa 3 students, the efficiency was 83.36/82.58. 2) Comparison of the competency to create innovation using creativity as a base for the students in Mathayomsuksa 3, overall, the students' level of innovation competency accounted for 82.58 percent, compared to the 70 percent criteria. The students' competency to create innovation was higher than the criteria. 3) Satisfaction with the learning activities using creativity as a base to promote the competency to create innovation for Mathayomsuksa 3 students, the overall level was at the high level ( = 4.53 , = 0.63).